2004
DOI: 10.1007/s00330-004-2422-1
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosed dialysis access grafts: randomized comparison of the Amplatz thrombectomy device and surgical thromboembolectomy

Abstract: We report the final results of the trial comparing the Amplatz thrombectomy device (ATD) with surgical thromboembolectomy (ST) to declot thrombosed dialysis access grafts (DAG). The study population consisted of 174 DAG, 109 of which were randomized to mechanical thrombectomy using the ATD and 65 of which were randomized to conventional surgical thromboembolectomy. Forty grafts were re-enrolled in the trial when they failed beyond the 90 days follow-up after the initial treatment. Thirty-one were re-enrolled f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Our study outcomes demonstrated the effectiveness of the technique, with 95% and 95% technical and clinical success rates, respectively. These results are comparable with previous reports using mechanical thrombectomy devices, which reported rates between 80% and 98% (19, 23-27). Moreover, our modified PMT technique results have acceptable post-interventional primary patency and secondary patencies, with low complication rates.…”
Section: Discussionsupporting
confidence: 91%
“…Our study outcomes demonstrated the effectiveness of the technique, with 95% and 95% technical and clinical success rates, respectively. These results are comparable with previous reports using mechanical thrombectomy devices, which reported rates between 80% and 98% (19, 23-27). Moreover, our modified PMT technique results have acceptable post-interventional primary patency and secondary patencies, with low complication rates.…”
Section: Discussionsupporting
confidence: 91%
“…A randomised study did not show any significant difference between surgical thrombectomy and endovascular treatment. 554 Additionally in a metaanalysis including six randomised trials surgical and endovascular therapy in AVGs were compared. It was concluded that endovascular therapy had similar results in terms of primary and primary assisted patency at 1 year compared with surgical thrombectomy.…”
Section: Thrombosismentioning
confidence: 99%
“…The results of the performance of both methods were comparable. No statistically significant differences were found 33 . It is clear that to correct an underlying outlet stenosis after thrombectomy AVG is important.…”
Section: Introductionmentioning
confidence: 75%